Contributing Factors of Dysphagia in Indonesian Elderly - Dias, Randi; Kusdhany, Lindawati S.; Indrasari, Muslita (European Journal of General Dentistry, 2024)
Objective Dysphagia is one of the signs that can describe oral hypofunction in the elderly. This condition is usually not noticed nor realized by the elderly and their families, resulting in disability and death. Studies on the relationship between age, gender, education, the number of systemic diseases, and the number of remaining teeth toward dysphagia in the elderly are still limited, so further research is needed. The aim of this study was to analyze the relationship between age, sex, education level, the number of systemic diseases, and the number of remaining teeth with dysphagia and find out which factors contribute the most to dysphagia. The contributing factors need to be known to minimize the risk of dysphagia.Materials and Methods This is a cross-sectional study with 121 elderly aged 60 years living in community dwellings as subjects of this study. General health data were obtained from anamnesis; demographic data were also collected and an examination of the number of remaining teeth was carried out and recorded on the odontogram by one researcher. After that, a dysphagia screening tool was given for self-assessment or assisted by the two researchers according to the conditions felt. Two researchers were calibrated before collecting data.Results In the bivariate analysis, age, the number of remaining teeth, and several systemic diseases were associated with dysphagia (p = 0.027, 0.023, and 0.047, respectively). No association was found between gender, education, and dysphagia status (p > 0.05). Age (p = 0.027), gender (p = 0.165), number of remaining teeth (p = 0.023), and the number of systemic diseases (p = 0.047) are the risk factors that were included in the multivariate model. From the final multivariate model, the number of remaining teeth (p = 0.017; odds ratio [OR] = 4.318), several systemic diseases (p = 0.036; OR = 2.427), and age (p = 0.072; OR = 1.962) contributed most to the dysphagia status, after controlling for confounding variables.Conclusion It is concluded that the number of remaining teeth, several systemic diseases, and age are the factors that contribute the most to the occurrence of dysphagia.
Keywords: elderly; dysphagia; age; number of remaining teeth; systemic diseases